Working from Density - Leah Brooks; Philip G. Hoxie; Stan Veuger (American Enterprise Institute (AEI), 2023)
Is the COVID-19 driven surge in remote work temporary or permanent? To assess how the geography of work may evolve, we analyze the pre-pandemic status quo. Casual theorizing might suggest that workers with teleworkable jobs in the pre-pandemic era were more likely to live in the less dense, peripheral neighborhoods in their metropolitan area. Instead, we find that, for neighborhoods of almost all incomes, those with a greater share of teleworkable jobs were likely to be relatively high-density. Potential explanations include the complementarity of reduced commuting time with urban amenities, and the complementarity of telework with social interactions outside the home.
Keywords: 330; Agglomeration; Amenities; Cities; Commuting; Telework; Work